Temporal Changes of Trust in Institutions Among Young Refugees in Germany: Insights from a Longitudinal Survey - Engel, Daniel (Refuge, 2026)
This longitudinal study examines trust in institutions among young refugees in Germany. Due to the scarcity of data, an initial exploratory approach was applied and the extent of trust in institutions is described; this is followed by a description of influencing factors on trust in institutions and developments over time. The central finding is that institutional trust initially is relatively high but erodes over time. A time-invariant positive effect at both measurement points is a sense of belonging to Germany. While in the earlier stages of arrival, perceptions of being in control is vital, later questions of purpose in life gain importance.